The magnitude, direction, and tempo of forest change in Greater Yellowstone in a warmer world with more fire. Issue 1 (4th November 2021) - Turner, Monica G.; Braziunas, Kristin H.; Hansen, Winslow D.; Hoecker, Tyler J.; Rammer, Werner; Ratajczak, Zak; Westerling, A. Leroy; Seidl, Rupert
Abstract: As temperatures continue rising, the direction, magnitude, and tempo of change in disturbance‐prone forests remain unresolved. Even forests long resilient to stand‐replacing fire face uncertain futures, and efforts to project changes in forest structure and composition are sorely needed to anticipate future forest trajectories. We simulated fire (incorporating fuels feedbacks) and forest dynamics on five landscapes spanning the Greater Yellowstone Ecosystem (GYE) to ask the following questions: (1) How and where are forest landscapes likely to change with 21st‐century warming and fire activity? (2) Are future forest changes gradual or abrupt, and do forest attributes change synchronously or sequentially? (3) Can forest declines be averted by mid‐21st‐century stabilization of atmospheric greenhouse gas (GHG) concentrations? We used the spatially explicit individual‐based forest model iLand to track multiple attributes (forest extent, stand age, tree density, basal area, aboveground carbon stocks, dominant forest types, species occupancy) through 2100 for six climate scenarios. Hot‐dry climate scenarios led to more fire, but stand‐replacing fire peaked in mid‐century and then declined even as annual area burned continued to rise. Where forest cover persisted, previously dense forests were converted to sparse young woodlands. Increased aridity and fire drove a ratchet of successive abrupt declines (i.e., multiple annual landscape‐level changes ≥20%) in tree density, basal area, and extent of older (>150 yr) forests, whereas declines in carbon stocks and mean stand age were always gradual. Forest changes were asynchronous across landscapes, but declines in stand structure always preceded reductions in forest extent and carbon stocks. Forest decline was most likely in less topographically complex landscapes dominated by fire‐sensitive tree species ( Picea engelmannii, Abies lasiocarpa, Pinus contorta var. latifolia ) and where fire resisters ( Pseudotsuga menziesii var. glauca ) were not already prevalent. If current GHG emissions continue unabated (RCP 8.5) and aridity increases, a suite of forest changes would transform the GYE, with cascading effects on biodiversity and myriad ecosystem services. However, stabilizing GHG concentrations by mid‐century (RCP 4.5) would slow the ratchet, moderating fire activity and dampening the magnitude and rate of forest change. Monitoring changes in forest structure may serve as an operational early warning indicator of impending forest decline.